The Relationship Between Exclusive Breastfeeding and Freguent Antenatal Care Visite with Stunting Incidence in Under-Fives in Sadai Village, Working Area Sungai Panas Primary Health Care Batam City - Roza, Neli; Huzaima; Yulinawati, Catur; Philip, Rofiqo Larasati (European Journal of Life Safety and Stability (2660-9630), 2023)
Stunting is a short and very short body condition that exceeds a -2 SD deficit below the median length or height. Stunting is a public health problem because it is associated with an increased risk of morbidity and mortality, delayed motor development, and stunted mental growth. The purpose of this research isthe relationship between exclusive breastfeeding and the frequency of antenatal care visits with the incidence of stunting is known and the dominant factor that causes stunting in toddlers is known. This study was a quantitative study with a Case Control design and involved 23 mothers whose toddlers were diagnosed with stunting as respondents (cases) and 23 mothers whose toddlers were not diagnosed with stunting (as controls). This research was conducted in the Sadai sub-district, the working area of the Sungai Panas Public Health Center in Batam.Data processing and analysis chi square test (bivariate) and multiple logistic regression (multivariate).The results of the analysis using the chi square test showed that there was a significant relationship between exclusive breastfeeding and the frequency of antenatal care visits with the incidence of stunting. The results of the multivariate analysis show variablesthe dominant influence on the incidence of stunting is the variable Frequency of Antenatal Care visits. The government, if it wants to reduce the prevalence of stunting in Sadai village, the working area of the Sungai Panas Health Center, should increase education to the public, especially pregnant women, about the importance of regular quality pregnancy checks according to the rules.